Exercise is medicine Canada workshop training improves physical activity practices of physicians across Canada, independent of initial confidence level - O'Brien, Myles William; Shields, Chris; Solmundson, Kara; Fowles, Jonathon (Canadian Medical Education Journal, 2020)
Background: Educational workshops help physicians (MDs) include physical activity and exercise (PAE) content in more patient appointments. It is unclear if MDs with varying degrees of self-confidence discussing PAE with their patients equally benefit from such training. We evaluated whether MDs’ initial self-confidence affects the impact of an educational PAE workshop. Methods: MDs (n = 63) across Canada completed self-reflection questionnaires initially and 3-months following a PAE workshop. MDs were divided into low-confidence [self-efficacy score (out of 100%): <40%; n = 21], medium-confidence (40-60%; n = 19) and high-confidence (>60%; n = 23). Results: PAE counselling self-efficacy increased in all groups (relative increase: Low=~40%, Medium=~20%, High=~10%). Training increased the low-confidence group’s knowledge, awareness of guidance/resources and perception of their patients’ interest in lifestyle management (~30% change; all p < 0.001). Compared to baseline, a greater proportion (all p < 0.001) of MDs reported prescribing exercise at 3-month follow-up in each of the low-confidence (10% to 62%) medium-confidence (16% to 89%) and high-confidence (57% to 87%) groups. Conclusion: PAE training favorably improved MDs’ self-confidence, perceived impact of many barriers and the proportion of MDs prescribing exercise, at each level of confidence. An educational workshop particularly assisted MDs with low-confidence (i.e., those who needed it the most) integrate PAE into their practice.